2007
DOI: 10.1186/cc6093
|View full text |Cite
|
Sign up to set email alerts
|

Positive end-expiratory pressure at minimal respiratory elastance represents the best compromise between mechanical stress and lung aeration in oleic acid induced lung injury

Abstract: IntroductionProtective ventilatory strategies have been applied to prevent ventilator-induced lung injury in patients with acute lung injury (ALI). However, adjustment of positive end-expiratory pressure (PEEP) to avoid alveolar de-recruitment and hyperinflation remains difficult. An alternative is to set the PEEP based on minimizing respiratory system elastance (Ers) by titrating PEEP. In the present study we evaluate the distribution of lung aeration (assessed using computed tomography scanning) and the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 39 publications
5
71
0
3
Order By: Relevance
“…It was found that E drs during increasing PEEP is significantly different to E drs during decreasing PEEP (p<0.005). Thus, this case shows the typical finding where PEEP should be titrated after the lung has been recruited [3][4][5]7]. However, a local minimum E drs was also found at 10 mbar during increasing PEEP titration, suggesting similar optimal PEEP settings.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…It was found that E drs during increasing PEEP is significantly different to E drs during decreasing PEEP (p<0.005). Thus, this case shows the typical finding where PEEP should be titrated after the lung has been recruited [3][4][5]7]. However, a local minimum E drs was also found at 10 mbar during increasing PEEP titration, suggesting similar optimal PEEP settings.…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, true minimal E drs can only be determined after a stabilisation period is provided at each PEEP level. Setting PEEP at minimum elastance theoretically benefits ventilation by maximising recruitment, reducing work of breathing and avoiding overdistension [3][4][5]9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 In an experimental study, hyperinflated regions of the lung shifted to normally aerated areas at PEEP levels of 8cmH 2 O (mean of 30% decrease) and yet hyperinflated areas still appeared at zero end expiratory pressure. 23 Hyperinflation of easily distensible regions of the lung is an acknowledged limitation of recruitment manoeuvres. 18,20,[22][23][24] How to recruit lungs?…”
Section: Whose Lungs Do You Recruit?mentioning
confidence: 99%
“…23 Hyperinflation of easily distensible regions of the lung is an acknowledged limitation of recruitment manoeuvres. 18,20,[22][23][24] How to recruit lungs?…”
Section: Whose Lungs Do You Recruit?mentioning
confidence: 99%